2005
DOI: 10.1021/ac050726j
|View full text |Cite
|
Sign up to set email alerts
|

Congruent Strategies for Carbohydrate Sequencing. 3. OSCAR:  An Algorithm for Assigning Oligosaccharide Topology from MSn Data

Abstract: This is the third in a sequence of reports devoted to the development of congruent strategies for carbohydrate sequencing. Two previous reports outlined the strategies for observing structural detail from MS n data and introduced tools that compile, search, and compare fragment spectra in a bottomup approach to oligosaccharide sequencing. In this third report, we introduce the operational details of an algorithm that we define as the Oligosaccharide Subtree Constraint Algorithm (OSCAR). This algorithm assimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 17 publications
1
93
0
Order By: Relevance
“…In these examples, we will use many of the concepts and tools previously described. 7,8,15,[26][27][28] All structures were derived de novo with input data from a single instrument.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these examples, we will use many of the concepts and tools previously described. 7,8,15,[26][27][28] All structures were derived de novo with input data from a single instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Structures, whether new or previously described, and their pathways were entered into GlySpy, a set of tools for data handling, complete with the glycan topology assignment algorithm, OSCAR. 28 Ion m/z fragmentation pathways used for OSCAR were selected manually by the analyst. OSCAR was then used to determine which of the isomeric structures were consistent with the fragmentation pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online derivatization coupled with LC/MS of permethylated oligosaccharide alditols has obvious advantages, and we are in the process of adapting online derivatization to the LC/MS platform. Reinhold et al have recently reported the complete assignment of oligosaccharide structures of permethylated glycans using a database library, FragLib, in conjunction with their Oligosaccharide Subtree Constraint Algorithm (OSCAR) [38,54,55]. This algorithm incorporates analyst-selected MS n ion fragmentation pathways for elucidation of oligosaccharide topology using a top-down sequencing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, there are differences in signal intensities, whereas in others, different fragment ions can be found. Accumulation of the spectral data in a database facilitates identification of oligosaccharides based on spectral matching [11][12][13][14][15][16][17]. An important problem-the elucidation of totally unknown structures that are not present in any databasewill still remain after the introduction of this efficient methodology.…”
mentioning
confidence: 99%